2019
DOI: 10.1002/hyp.13443
|View full text |Cite
|
Sign up to set email alerts
|

Time‐varying, nonlinear suspended sediment rating curves to characterize trends in water quality: An application to the Upper Hudson and Mohawk Rivers, New York

Abstract: This work proposes two modelling frameworks for diagnosing temporal variations in nonlinear rating curves that describe suspended sediment–discharge relationships. A variant of the weighted regression on time, discharge, and season model is proposed and is compared against dynamic nonlinear modelling, a newly developed nonlinear time series filter based on sequential Monte Carlo sampling. Both approaches estimate a time series of rating curve parameters, with uncertainty, that can be used to diagnose variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 54 publications
(95 reference statements)
0
14
0
Order By: Relevance
“…To evaluate the influence of the variability in watershed inputs, we also calculated the residual of the LOWESS regressions of log 10 ( SSC ) versus log 10 ( Q r ) for the tributaries on an annual basis. Precipitation from Irene and Lee was focused in the Mohawk watershed and the Catskill Mountains east of the Hudson, leading to mass wasting, increased erosion, and potential hysteresis in the sediment‐discharge relationship for these regions (Ahn & Steinschneider, 2019). In water years 2012–2014 following the events, the average SSC in the Mohawk increased by a factor of about 1.2 above the regression values, but the Mohawk turbidity ratio was not significantly correlated with the turbidity ratios in the estuary.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate the influence of the variability in watershed inputs, we also calculated the residual of the LOWESS regressions of log 10 ( SSC ) versus log 10 ( Q r ) for the tributaries on an annual basis. Precipitation from Irene and Lee was focused in the Mohawk watershed and the Catskill Mountains east of the Hudson, leading to mass wasting, increased erosion, and potential hysteresis in the sediment‐discharge relationship for these regions (Ahn & Steinschneider, 2019). In water years 2012–2014 following the events, the average SSC in the Mohawk increased by a factor of about 1.2 above the regression values, but the Mohawk turbidity ratio was not significantly correlated with the turbidity ratios in the estuary.…”
Section: Resultsmentioning
confidence: 99%
“…Watershed sediment supply depends in part on revegetation of landslides and bank failures, which adjusts at multiyear time scales (Dethier et al, 2016; Gray et al, 2014; Yellen et al, 2014). Watershed sediment supply from the Mohawk increased relative to discharge during 2012–2014 due to these geomorphic adjustments in its steep tributaries (Ahn & Steinschneider, 2019) and thus may contribute to the 2012–2013 increase in the turbidity factor in the tidal river (Figure 4d). However, we observed a similar increase in the SSC factor relative to the discharge relation for the Mohawk in 2017, when the turbidity factors at tidal river stations were less than or equal to 1.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DLMs allow linear rating curve parameters to be updated over time in response to model prediction errors using a recursive Bayesian algorithm. Different variants of this model structure were also proposed to accommodate future scenarios of discharge (Ahn and Steinschneider 2017) and nonlinear rating curve relationships (Ahn and Steinschneider 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, Kiang et al (2018) concluded that one way to reduce the uncertainty in discharge curves estimations is by selecting a stable section, since this reduces the number of discharge curves over time and, therefore, a smaller number of curves accounts for a more stable bed. Likewise, Ahn and Steinschneider (2019) noted that the value of the intercept for sediment discharge curve models tested in the Hudson River (NY) decreased after the declaration of the Clean Water Act, inferring that this can be explained in terms of the decrease in agricultural area, the increase in wetlands, and the corresponding decrease in sediment production.…”
Section: Introductionmentioning
confidence: 99%